A COACHING MODEL OF THE PEDAGOGIC COMPETENCE OF HONORARIUM TEACHERS IN REMOTE AREAS (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
Many civil servant teachers in remote primary schools were absent, so honorary teachers played an important role in learning. According to SEMERU Research Institute data, 31% of remote teachers who were absent were special beneficiaries (Kompas, 2016). The problem is that temporary teachers in remote primary schools are only high school graduates, and some even junior high schools. therefore an adaptive competency coaching model was needed. This must be done otherwise, the learning process in remote primary schools will not be effective. The purpose of this study was to examine the effectiveness of the adaptive coaching model of competence to optimize the competence of honorary teachers in remote primary schools. It first introduces the background and rationale for the project. Action research with an experimental model was used in this study. The results of the study explain that the adaptive coaching model can improve the competence of teacher honorariums in remote areas. Therefore, learning in remote schools were becomes more conducive than before.